PSX-12 Effects of dietary supplementation with α-terpineol on growth performance and intestinal functions in piglets challenged with recombinant E. coli strain LMG194-STa. (7th December 2018) - Yi, D; Xu, H; Hou, Y; Wang, L; Zhao, D; Wu, T; Ding, B; Wu, G
Abstract: This study is conducted to investigate the effects of dietary supplementation with α-terpineol (Ter) on growth performance and intestinal functions in piglets challenged with recombinant E. coli strain LMG194-STa (STa). Twenty-four piglets were assigned randomly into one of the three groups: control group [fed with basal diet and administrated with sterile saline], STa group [fed with basal diet and administrated with STa (established by Wu et al. 2018)], and STa+Ter group [fed with basal diet supplemented with 100 mg/kg α-terpineol (Sigma-Aldrich) and administrated with STa]. On day 14 of the trial, piglets in the STa and STa+Ter groups were administrated orally with 5 ml STa (1010 CFU), while those in the control group were administrated orally with the same volume of sterile saline. Blood and intestinal samples were collected on day 15 of the trial. Compared with the control group, STa challenge increased (P < 0.05) the diarrhoea incidence (75% vs. 12.5%), the number of eosinophils (+105%) and TNF-α concentration (+106%) in plasma, the number of Enterobacteriaceae family (+296%) and Clostridium coccoides group (+67%) in the colon, malonaldehyde level (+58%) and myeloperoxidase activity (+65%) in the jejunum, mRNA level for glutathione S-transferase omega-2 (+361%) in the jejunum, and caspase-3 (+79%) and HSP70 (+62%) protein abundances in the jejunum, but reduced (P < 0.05) villus height (-15%) and villus height/crypt depth ratio (-27%) in the ileum, the number of Lactobacillus genus (-88%) in the caecum, and protein amounts of occludin (-56%) and aquaporin 3 (-38%). However, these adverse effects of STa were alleviated by Ter supplementation. Additionally, Ter supplement increased (P > 0.05) the ADFI and ADG in STa-challenged piglets by 18% and 19%, respectively, in comparison with the control group. In conclusion, dietary supplementation with Ter increased the growth performance and alleviated the intestinal damage in piglets challenged with STa. Key Words: